Old Age and Co Residence in Popular Sectors: The Case of Older Women and Their Adult Children; [Vejez y Coresidencia en Los Sectores Populares: El Caso de Las Mujeres Mayores E Hijos/As Adultos/As] - Andrade-Orrego, C (Universidad Austral de Chile, 2024)
The aim of this article is to present the results of a qualitative study on co-residencies in old age of women and their adult children from the popular sectors of Santiago, Chile. Some discussions about old age and co-residencies in the international and Chilean context are presented. The results of the interviews with older women, and their adult children point out how positive it is for women to live with their adult children in terms of company, while adult children highlight the economic, emotional and care support, with significant differences depending on the gender. In general, the negative aspects are more highlighted by sons and daughters, associated with the control that mothers exercise over their activities and relationships, causing conflict scenarios with men. © 2024, Universidad Austral de Chile. All rights reserved.